2014
DOI: 10.1111/ejh.12271
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 and IDH2 mutations confer an adverse effect in patients with acute myeloid leukemia lacking the NPM1 mutation

Abstract: We examined the incidence and prognostic effect of IDH1 and IDH2 mutations in 233 Japanese adults with acute myeloid leukemia (AML). IDH1 R132 mutations were detected in 20 (8.6%) patients with AML. IDH2 mutations were found in 19 (8.2%, 17 R140 and two R172) patients. IDH1 and IDH2 mutations were mutually exclusive and were associated with normal karyotype AML, cytogenetic intermediate-risk group, and NPM1 mutations. Five-year overall survival (OS) rates were significantly lower (15.6%) in patients harboring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 39 publications
5
28
1
Order By: Relevance
“…Previous studies of IDH1 mutations on outcome after IC have reported either no impact on or an increased rate of disease recurrence. [37][38][39] Therefore, our data demonstrating a reduced risk of relapse after allo-SCT in patients with an IDH1 mutation raise the possibility that the genetic factors determining outcome after IC may differ from those determining relapse after allo-SCT.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies of IDH1 mutations on outcome after IC have reported either no impact on or an increased rate of disease recurrence. [37][38][39] Therefore, our data demonstrating a reduced risk of relapse after allo-SCT in patients with an IDH1 mutation raise the possibility that the genetic factors determining outcome after IC may differ from those determining relapse after allo-SCT.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, in the aspect of FAB classification, patients with M1 harbored higher percentage of IDH mutations (6,17,18,24,25,29,30,39,42), whereas in cases with M4, lower percentage was observed (17,24,29,47). Besides, the frequency of IDH mutations was higher in cases with normal karyotype in 9 studies (6, 16-18, 24, 25, 29, 30, 39, 40, 42, 48).…”
Section: Study Characteristicsmentioning
confidence: 91%
“…As shown in Supplementary Table S1, IDH gene aberrations were closely associated with elderly patients in 12 studies (16, 18, 25, 26, 30, 32, 33, 38, 41-43, 47, 48) and with higher platelet count in 9 studies (16,18,26,27,29,36,38,42,43). In addition, in the aspect of FAB classification, patients with M1 harbored higher percentage of IDH mutations (6,17,18,24,25,29,30,39,42), whereas in cases with M4, lower percentage was observed (17,24,29,47).…”
Section: Study Characteristicsmentioning
confidence: 93%
“…The aggregate frequency of these two mutations in AML is relatively high, approximately 15-20% of all patients with AML and 25-30% of patients with CN-AML harboring either IDH1or IDH2mutations respectively [27]. Different studies have reported the IDH1/2 mutational status in AML patients and a statistically significant co-occurrence with NPM1 and CEBPA mutations [137]. In the two consecutive studies correlations IDH1/2 mutations with outcome in AML, except for the IDH1/2 mutation enrichment in the NPM mutant group, it was reported that patients with the IDH-R140 mutation had an improved OS and decreased response rates.…”
Section: Idh1/2 Mutationsmentioning
confidence: 99%
“…However it has been observed that IDH-mutant AMLs have a unique methylation profile characterized by global promoter hypermethylation, which provides these cases reasonable candidates for demethylation therapies [141]. Recent finding suggested that allogeneic HSCT may improve OS in younger patients with IDH mutations [137]. However, patient numbers who underwent allogeneic HSCT were small; the efficacy of allogeneic HSCT should be verified in large cohort of patients with IDH mutations…”
Section: Idh1/2 Therapeutic Implicationmentioning
confidence: 99%